Building informative audio-visual content automatically: a process to define the key aspects - Silva, Telmo (2018)
Related to the population ageing that most of the countries are witnessing, several new challenges emerged in areas such as health and social care. Often, governments and entities does not have human, physical and infrastructural means available or in sufficient number to support all citizens’ needs. This trend requires different approaches to address their related problems. In this context, several technologies have recently emerged and have been explored as an important ally to cope with seniors’ needs. Interactive television (iTV) infrastructure have a lot of potential to deliver adapted solutions to seniors, although it is essential that such products are designed and developed with inputs from potential end users. The application of a participatory design approach is a key factor to assure high levels of final products’ adoption. In line with this, the present paper describes the process of data collection that aims to analyse the audio-visual elements that compose a set of videos that will be transmitted by an iTV platform and that intents to deliver informative contents about social and public services to Portuguese elders. The results will provide guidelines for the development of similar products that address older people’s needs.